2016
DOI: 10.1021/acs.energyfuels.5b02280
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Looping Hydrogen Generation Using Potassium-Modified Iron Ore as an Oxygen Carrier

Abstract: Chemical looping hydrogen generation (CLHG) consists of an oxidation process, a reduction process, and a hydrogen generation process. Achieving deep reduction of the oxygen carrier is the challenge for the CLHG process. In this paper, experiments on CLHG using K-modified iron ore as an oxygen carrier and CO as a fuel were carried out in a laboratoryscale fluidized bed reactor. A high temperature improved the reduction reactivity. However, at the same reduction condition, a higher temperature did not improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 38 publications
0
34
1
Order By: Relevance
“…As discussed above, the carbon deposition was significantly suppressed by introducing potassium and copper to modify iron ore. The similar effect was also observed when iron‐based oxygen carrier was modified by copper or potassium separately . It was the first work to investigate the property of carbon deposition based on iron ore co‐decorated by potassium and copper, and the condition was different from most of the previous researches .…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…As discussed above, the carbon deposition was significantly suppressed by introducing potassium and copper to modify iron ore. The similar effect was also observed when iron‐based oxygen carrier was modified by copper or potassium separately . It was the first work to investigate the property of carbon deposition based on iron ore co‐decorated by potassium and copper, and the condition was different from most of the previous researches .…”
Section: Resultsmentioning
confidence: 65%
“…These Fe‐Cu‐K solid solutions would be formed during the calcining process. There were few studies considering the property of K 4 CuO 3 , but many researches had reported that K 2 Fe 4 O 7 and CuFe 2 O 4 were active phases to improve the reactivity and deepen reduction of iron oxides . (3) Additionally, the migration of potassium and copper made the oxygen carrier particle more porous, and it was beneficial to enhance the reduction rate .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations